Analysis of Performance, Commitment, and Self-concept of Physical Education Teachers in Tanjung Pura-Langkat District (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to analyze the Performance, Commitment, and Self-concept of Physical Education Teachers in Tanjung Pura-Langkat District. This research method uses qualitative methods with ethnographic design. Data collection techniques using interviews, observation, documentation, and questionnaires. The research subjects were 12 physical education teachers, consisting of 7 teachers who were not physically educated, and five teachers with a physical education background in Public Elementary School Tanjung Pura-Langkat District; secondary data are principals and coworkers. Data analysis techniques include data reduction, data presentation, and drawing conclusions/verification. The results showed that the performance of physical education teachers in Public Elementary School Kecamatan Tanjung Pura-Langkat had not shown satisfactory results, motivated by factors educational backgrounds that are not in accordance with their fields that automatically hinder the performance of the teacher, the limitation of physical education teaching staff, which requires the school to take steps to use the services of a teacher with a background not physical education. Conclusion: research, performance, and self-concept of physical education teachers who have physical education background are better than physical education teachers who are not physically educated.